Proceedings of the 12th ACM Workshop on Multimedia and Security 2010
DOI: 10.1145/1854229.1854259
|View full text |Cite
|
Sign up to set email alerts
|

Reversible watermarking for image integrity verification in hierarchical PACS

Abstract: Reversible digital watermarking has been indicated as the technology to be adopted when image security is to be granted in a medical application scenario. The work presented hereafter provides a new lossless watermarking algorithm designed to really be integrated in a Picture Archiving and Communication System matching the requirements coming from radiological experts. The proposed technique has been developed by modifying and improving the methodology implemented in [3]. Experimental results carried out on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The process of integrating the proposed watermarking technique into medical environments is then clarified and validated. Two studies have been found; one related to manipulation of medical images within PACS database [5] and another study related to tampering with medical images during transmission [13]. In addition, two potential security issues have also been identified in this research.…”
Section: Validation Of the Proposed Medical Imaging Workflowmentioning
confidence: 86%
See 2 more Smart Citations
“…The process of integrating the proposed watermarking technique into medical environments is then clarified and validated. Two studies have been found; one related to manipulation of medical images within PACS database [5] and another study related to tampering with medical images during transmission [13]. In addition, two potential security issues have also been identified in this research.…”
Section: Validation Of the Proposed Medical Imaging Workflowmentioning
confidence: 86%
“…These threats need to be identified first to provide a secure platform for medical imaging workflow that can address these threats. To achieve this, a research paper has been considered as a case study to identify security risks that may face medical images stored in the PACS database [5]. This aids in analyzing the PACS workflow and understanding the security requirements derived from the medical side to determine a suitable approach for integrating the proposed watermarking technique into medical domains.…”
Section: Scenario Four (S4) -Archiving Phasementioning
confidence: 99%
See 1 more Smart Citation
“…We now briefly describe the AO-PEE embedding procedure as follows. First, for a cover pixel x i , if its complexity measurement n i < T , the prediction-error e i is modified according to (6) to get e i . Then, x i is modified to x i = x i + e i to get the marked pixel.…”
Section: Ao-peementioning
confidence: 99%
“…Images captured in a hospital are inserted into the Picture Archiving and Communication Systems (PACS) and then transferred to the hierarchically upper PACS systems until they reach the top-PACS. In the top-PACS, the data is permanently archived in tapes, physical drives, or optical supports to become available for the diagnostic workflow services through drawdown within the PACS system [2].…”
Section: Introductionmentioning
confidence: 99%